The vaginal microbiota, human papillomavirus and cervical dysplasia: a systematic review and network meta‐analysis. (17th July 2019) - Norenhag, J; Du, J; Olovsson, M; Verstraelen, H; Engstrand, L; Brusselaers, N
Abstract : Background: Persistent infection with high‐risk human papillomavirus can lead to cervical dysplasia and cancer. Recent studies have suggested associations between the composition of the vaginal microbiota, infection with human papillomavirus (HPV) and progression to cervical dysplasia and cancer. Objective: To assess how specific cervico‐vaginal microbiota compositions are associated with HPV infection, cervical dysplasia and cancer, we conducted a systematic review and network meta‐analysis (registered in PROSPERO: CRD42018112862). Search strategy: PubMed, Web of science, Embase and Cochrane database. Selection criteria: All original studies describing at least two community state types of bacteria (CST), based on molecular techniques enabling identification of bacteria, and reporting the association with HPV infection, cervical dysplasia and/or cervical cancer. Data collection and analysis: For the meta‐analysis, a network map was constructed to provide an overview of the network relationships and to assess how many studies provided direct evidence for the different vaginal microbiota compositions and HPV, cervical dysplasia or cancer. Thereafter, the consistency of the model was assessed, and forest plots were constructed to pool and summarise the available evidence, presenting odds ratios and 95% confidence intervals. Main results: Vaginal microbiota dominated by non‐ Lactobacilli species or Lactobacillus iners were associated with three to five times higher odds of any prevalent HPV and two to three times higher for high‐risk HPV and dysplasia/cervical cancer compared with Lactobacillus crispatus . Conclusions: These findings suggest an association between certain bacterial community types of the vaginal microbiota and HPV infection and HPV‐related disease. This may be useful for guiding treatment options or serve as biomarkers for HPV‐related disease. Tweetable abstract: This network meta‐analysis suggests an association between different vaginal bacterial community types and the risk of HPV. Tweetable abstract: This network meta‐analysis suggests an association between different vaginal bacterial community types and the risk of HPV.